THE EFFECT OF WORK EXPERIENCE ON INTERNAL AUDIT QUALITY WITH AUDITOR COMPETENCE AS AN INSPECTORATE INTERVENING VARIABLE BINJAI CITY AREA - Eka Edi Saputra; Kiki Farida Ferine (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
This study aims to analyze the effect of work experience on internal audit quality with auditor competence as an intervening variable. This type of research is associative quantitative research. The research was conducted at the Binjai City Inspectorate office. The population used in this study was 79 employees and the sample used was all populations counted without exception of 79 employees. The sample technique used was the saturated sample technique. The data collection used is by distributing questionnaires. The research model used is path analysis and the measuring tool used is Smart PLS version 3.3.3. The result of his research is that competence has a positive and significant effect on audit quality. Work Experience has no significant positive effect on competence. Work Experience has no significant negative effect on Audit Quality.